Sale of Merchantable Quality Goods in Today’s Online Contract: Issues and Challenges - Asuhaimi, Farhanin Abdullah; Ghadas, Zuhairah Ariff Abd; Nawang, Nazli Ismail (Indonesian Comparative Law Review, 2022)
Nowadays, many consumers choose to buy their needs using online platforms rather than the traditional method. The transactions became more active during the Covid-19 pandemic when the citizen movement was restricted with the enforcement of the Movement Control Order. Thus, the online platform needs to provide good information on the product to gain consumers' confidence in entering into any online transactions. This paper highlights the principles of sale of merchantable quality goods in the Malaysia Sale of Goods Act 1957(SOGA) and the consequences of the breach based on a systematic literature review. This paper also investigates the application of the sale of merchantable quality goods in online platforms using the method of content analysis. This research revealed that Lazada and Shopee, as Malaysia's most clicked e-commerce platforms, successfully protect their ranking by providing a perfect practice in ensuring the goods sold comply with the merchantable quality as in SOGA. However, as consumers must be aware of the underlying principle of caveat emptor thus, this paper concludes with some tips for buying online and the suggestion for the online platform to ensure the practice is in line with the current law in Malaysia.